Integrating E-Recruitment and Employer Branding in Explaining Generation Z’s Job Application Intentions - Najmalia, Salsabila; Ardansyah (Jurnal Ilmu Manajemen, 2026)
The rapid development of digital technology has transformed recruitment practices through the adoption of e-recruitment systems and the strengthening of employer branding. As a digital-native generation, Generation Z has distinct preferences and expectations in the job application process. The intention of the current research is to investigate how employer branding and e-recruitment affect Generation Z's tendency to send applications for jobs in Bandar Lampung. A quantitative research approach was employed using a survey method. Multiple linear regression using SPSS version 26 was used to examine the data gathered from Generation Z respondents via online questionnaires. The results indicate that e-recruitment has a positive and significant effect on job application intention. Additionally, Generation Z's intention to apply for jobs is positively and significantly impacted by employer branding. Employer branding and e-recruitment both have a significant impact on the intention to apply for jobs. This study concludes that effective digital recruitment systems and a strong, positive employer image are essential strategies for organizations seeking to attract Generation Z in the modern labor market.